16th international conference on dependability and quality management ICDQM-2013 (proccedings review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The article presents the basic information about overal results, significance, international programme committee and working areas of the 16th International Conference on Dependability and Quality Management ICDQM-2013 and 4th International Conference on Life Cycle Engineering and Management, held under the same acronym ICDQM-2013. This year conference has had the biggest number of papers so far. The number and structure of papers of both conferences are given, as well as a review of the papers presented only by the participants from the Armed forces and the Ministry of Defense of the Republic of Serbia as plenary lectures and in Sections: Quality Engineering, Reliability Engineering, Concurrent Engineering, Systems Engineering and Military Engineering.
Keywords: conferences; review; military engineering; reliability; quality